News patterns of Malaysia’s online news platform during movement control order / Li Cheng Lim and Yoke Ling Loh - Lim, Li Cheng; Loh, Yoke Ling (Universiti Teknologi MARA, 2022)
In Malaysia, the Movement Control Order (MCO) prevents individuals from leaving home during the outbreak of COVID-19, and most of them rely on online media for news. The relevance of the news to the viewer, the audience's interest, and the sense of engagement that the news audience seeks are all reflected in Facebook's posting of news pattern through comments, sharing, and tagging friends. The result could assist in the effectiveness of news diffusion in future. Quantitative content analysis was used in this study to analyses the news patterns on the news coverage of the COVID-19 pandemic between the Facebook fan page of Malaysiakini, Astro Awani, and Sin Chew Daily during the outbreak of the COVID-19 pandemic. Purposive sampling used in this research to ensure the news related to COVID-19. The sampling period is the first phase of MCO (18th March 2020 – 31st March 2020). Framing theory is used by online news organisations to deliver the news. In general, these online news organisations frame the news with different news patterns, including news slants, dimensions of news and news values. Study revealed that there was more neutral news within the first phase of MCO, followed by alarming news, reassuring news, and balanced news. In addition, news audiences in Malaysia are more focused on the news with serious, up-to-date, and tragic content.